ANALISIS DAMPAK DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, LEVERAGE DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Lieany, Lieany; Abraham, Matius; Valencia, Marcellina; Meiden, Carmel (JURNAL ADMINISTRASI KANTOR; Vol 10 No 2 (2022): Jurnal Administrasi Kantor (Desember 2022)DO - 10.51211/jak.v10i2.2159, 2023)
The purpose of this study is to analyze the effect of recently selected variables, including the independent board of commissioners, audit committee, leverage and profitability on earnings management, because in carrying out the management function it is necessary to balance it with good corporate governance. In this study, researchers focus on corporate governance on independent commissioners and audit committees, other factors such as leverage and profitability as the basis and key to improving company results. This study uses the Modified Jones Model to determine the effect of earnings management. Purposive sampling is used in the sampling technique. Data collection is based on secondary data published in 2011-2022 with the help of meta analysis. The results of the study partially show (t test) that the independent board of commissioners, audit committee, leverage and profitability have a positive effect on earnings management.   Keywords : Board of commissioners, Audit committee, Good corporate governance, Profitability, Leverage, Earnings Management.